Analisa Perbandingan Biaya Material Pasangan Bata Merah, Bata Ringan dan Batako pada Proyek Pembangunan Museum MPU Purwa Malang - Asuat , Fransiska Romana ; Arifianto, Andy Kristafi ; Wijaya , Handika Setya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Wall is a building element that functions to separate and form space. As technology advances, many choices of materials are used to save the cost and time of wall installation work. Productivity enhancement activities are an effort to improve the value of productivity that has been planned, wherein this activity requires field data. Labor and high volume of work will certainly require high costs so that a good level of productivity will minimize project costs and optimal work time. The object of the research is MPU Purwa Building, Malang City with an average brick wall area of ??107.48 m2 and the second floor masonry wall area is 58.47 m2. The working group determined as many as 3 groups according to the type of masonry used and with each combination was group 1 with 1 worker 2 workers, group 2 with 1 worker 2 workers, and group 3 with 1 worker 2 workers and group 4 with 1 worker 2 workers. Research observations were carried out with a total of 3 days of observation. Research analysis is carried out on the productivity and efficiency of each working group. The most optimal working group in terms of cost is work group 3 with a combination of 1 worker and 2 workers. This working group has a cost of Rp 88,186,456.01. Whereas the most optimal working group in terms of time is working group 2 with a combination of 1 worker and 2 workers. This working group has a work completion time of 1 m2 for 5 working days compared to other work groups.